2018
DOI: 10.1093/milmed/usx186
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Investigation of Neurotrauma Serum Biomarkers, Behavioral Characterization, and Brain Imaging in Soldiers Following Repeated Low-Level Blast Exposure (New Zealand Breacher Study)

Abstract: "Breachers" (dynamic entry personnel) are routinely exposed to low-level blast overpressure during training and occupational duties. Data were collected from 22 military breachers (mean 29.7 yr) over a 5-yr period to characterize the longitudinal effects of repeated low-level blast overpressure exposure. None of the participants reported a diagnosed concussion during the study period. Blood-based biomarker concentrations (n = 22) showed either no significant change or a significant decrease over time. Neurocog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 12 publications
0
17
1
Order By: Relevance
“…Anecdotally, adherence to personnel protective equipment (PPE) usage may not be consistent across units and personnel, and is a point of further investigation. This data is at odds with previous findings from a breacher population, however, the total number of exposures (2–4 maximum) are far fewer in the breacher setting on a given day (16). Without the information about the exposure conditions, such as OP or acoustic pressure and stand-offs distances, it is hard to make meaningful comparisons.…”
Section: Conclusion/summarycontrasting
confidence: 95%
See 2 more Smart Citations
“…Anecdotally, adherence to personnel protective equipment (PPE) usage may not be consistent across units and personnel, and is a point of further investigation. This data is at odds with previous findings from a breacher population, however, the total number of exposures (2–4 maximum) are far fewer in the breacher setting on a given day (16). Without the information about the exposure conditions, such as OP or acoustic pressure and stand-offs distances, it is hard to make meaningful comparisons.…”
Section: Conclusion/summarycontrasting
confidence: 95%
“…Personnel Assessment Pre and post personnel assessments were conducted over a single day of data collection (prior to blast/training, end of day/training) using previously established symptom metrics (3, 9, 10, 16) that employed a five-point likert-type scale ranging from 0- did not experience the symptom at all, to 4- a severe problem—constantly present, feels like it could affect individual's performance. Subjects were all male and averaged 30.34 + 4.93 years old (min 24, max 36) and 11.5 + 4.92 years of service (min 6, max 15.5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Military personnel are often exposed to blast overpressure during training with explosives as well as heavy (e.g., mortars, rockets & machine guns) and light (rifles & pistols) weapons and during combat [1,2]. Recent research has demonstrated that exposure to blast overpressure can result in deficits in neurocognitive performance [3,4] and changes in blood biomarkers [5][6][7][8][9] in the absence of a medically diagnosable injury such as concussion. At present any acute or subacute reported symptoms short of a medically diagnosed injury are not entered into an individual's medical record or other service records.…”
Section: Introductionmentioning
confidence: 99%
“…The early confirmation connecting the LLB with neurological abnormalities are the studies on breachers, which were reported more than a decade ago by operating independently military medical providers from multiple countries (2). The cluster of subjective symptoms described as “breacher's brain” including a headache, fatigue, a slowed thought process and an increase in memory deficits bear a striking resemblance to symptoms of concussion (2, 810). These reports led to several blast exposure studies which focused on outcome measures (e.g., biomarkers, neuroimaging, cognitive performance, and symptom reporting).…”
Section: Introductionmentioning
confidence: 99%